Formulações matriciais à base de quitosana : estudos de adsorção e liberação de corantes. - Lemos, Cristiane Campos (2012)
Spheres of chitosan were prepared and crosslinked with sodium tetraborate and the epoxy resin PY-340 to obtain the hybrid materials QUIT-BORAX and QUIT-EPOXI, respectively. The hybrid QUIT-EPOXI was reacted with sodium tetraborate to obtain the hybrid QUIT-EPOXI-BORAX. The spheres of raw chitosan and the new hybrid materials were characterized by determining the pH of zero point charge, thermogravimetry, infrared absorption spectroscopy and scanning electron microscopy. Interactions processes of the dyes methylene blue (AM) and remazol Red (VR) with the hybrids were evaluated using adsorption tests in acidic and alkaline media (pH 4 and pH 10 buffered solutions, respectively) at 30 °C. In the tests of AM adsorption using AM initial concentration of 8.8 mg L-1 in pH 10 buffered solution, the AM adsorbed amounts on QUIT BORAX, QUIT-EPOXY and QUIT-EPOXY-BORAX were 1.438, 1.970 and 1.385 mg g-1, respectively. These values correspond, respectively, to 32.81%, 35.49% and 31 70%, indicating the following affinity order for AM adsorption: QUIT-EPOXY > BORAX-QUIT > QUIT-EPOXY-BORAX. In the interactions of the VR dye (initial concentration of 6.3 mg L-1, pH 4 buffered solution) with the materials, this dye was only adsorbed on the QUIT-BORAX-EPOXY material with an adsorbed amount, of 1.808 mg g-1, corresponding to 58.21% of removal of VR. It was observed that the materials have not affinity for AM in pH 4, and the VR dye was not adsorbed on the materials using pH 10 buffered solution. The best release results of the impregnated AM indicated the following dye release order: QUIT-EPOXY-BORAX (74.7%) > QUIT-BORAX (64.1%) > QUIT-BORAX (41.8%), during approximately seven days. The experiments have shown that the obtained hybrid materials can be used in the application of cationic species in carrier systems.